2019
DOI: 10.1371/journal.pone.0216037
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies with an outcome of fetal death present higher risk of delays in obstetric care: A case-control study

Abstract: The objective of this study was identify the association between delays in the care provided to pregnant women and the fetal death outcome, in a tertiary reference maternity hospital in the Northeastern Brazil. A case-control study, with 72 cases of fetal death and 144 controls (live births) in women admitted to the Obstetrics Service of the Assis Chateaubriand Teaching Maternity Hospital, in Fortaleza, Ceará. Controls were matched (2:1) by the approximate gestational age of the case. The groups were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
3
6
1
1
Order By: Relevance
“…During the study period, there were 28,580 deliveries , out of which 520 stillbirths occurred making the average stillbirth rate 18.19 per 1000 total births which was higher compared to a study by Dandona R et al in an Indian state where a SBR of 15.4/1000 births has been reported during 2017 [9] . However, SBR in our study was quite low compared to a study at a tertiary hospital in Brazil in 2017, where a SBR of 21.6 has been reported [10] . A downward trend in the SBR was observed, being 22.86%, 15.55% and 14.51% in the year 2016, 2017 and 2018 respectively (Table 1, Fig 1).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…During the study period, there were 28,580 deliveries , out of which 520 stillbirths occurred making the average stillbirth rate 18.19 per 1000 total births which was higher compared to a study by Dandona R et al in an Indian state where a SBR of 15.4/1000 births has been reported during 2017 [9] . However, SBR in our study was quite low compared to a study at a tertiary hospital in Brazil in 2017, where a SBR of 21.6 has been reported [10] . A downward trend in the SBR was observed, being 22.86%, 15.55% and 14.51% in the year 2016, 2017 and 2018 respectively (Table 1, Fig 1).…”
Section: Discussioncontrasting
confidence: 90%
“…It has been documented that women with no prenatal care had significant increased risk of stillbirths [15] and is a determinant factor associated with the occurrence of fetal deaths [10] . Similar results were revealed in our study that 54.81% of women were unbooked and had no or inadequate prenatal care (Table2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on the same subject that aimed to identify the association between delayed obstetric care and fetal death outcomes reported that the first, second, and third delays contributed to these outcomes [18], showing that delays in maternal care at any levels increase the chances of perinatal complications. We believe that neonatal morbimortality cannot be attributed to a single delay, but to a combination of factors that lead to an unfavorable outcome.…”
Section: Discussionmentioning
confidence: 99%